EXPLORING ENGLISH TEACHERS’ TECHNOLOGY-BASED ASSESSMENT LITERACY AND PRACTICES IN INDONESIAN SECONDARY EDUCATION - Sheila Agustina; Fika Megawati (Academic Journal Research, 2026)
Objective: This study explores how English teachers engage with technology-based assessment in Indonesian secondary education, with particular attention to their perceptions, practices, and evaluative approaches. Method: Using an exploratory mixed-method design with a qualitative-dominant orientation, data were collected from ten Senior High School English teachers through a questionnaire consisting of closed-ended and open-ended items. Results: The findings reveal that teachers have widely integrated digital tools, such as Google Forms, ChatGPT, and Grammarly, into their assessment practices, primarily to improve efficiency, automate grading, and provide feedback. However, their engagement with technology is largely operational, with limited conceptual differentiation between AI-driven and non-AI tools. Teachers frequently categorize diverse technologies under a broad notion of “AI,” indicating a functional rather than conceptual understanding. Despite this ambiguity, teachers maintain a strong reliance on human judgment, using technology-generated outputs as references rather than final decisions. The study also identifies an emerging but incomplete critical awareness, as teachers recognize concerns related to accuracy and bias while continuing to use these tools in practice. These findings suggest that teachers’ technology-based assessment literacy is unevenly developed, with strong operational competence but evolving conceptual and critical dimensions. Novelty: The study highlights the need for professional development that moves beyond technical training toward fostering informed, reflective, and ethically grounded engagement with technology in assessment.